Analysis of the effectiveness and benefits of tafsir "Tafheem ul Quran" and tafsir "Fi-Dhilal il-Quran" in the preaching of Islam in Modernage: عصر جديد میں اسلام کی مؤثر دعوت کے لئے تفسیر تفہیم القرآن اور تفسیر فی ظلال القرآن کی معنویت کا علمی جائزہ - Amjad Hayat, amjad; Muhammad Saeed, muhammad saeed (AL-IDRAK JOURNAL, 2021)
This research paper studies the effectiveness of Tafheem ul Quran and Fi-Dhilal il-Quran in the preaching of Islam in the modern age the one is written by Syed Abul Aalaa Maududi (1903A.D – 1979 A.D) a great revivalist, religious scholar, reformer, academia and representative of Islam, while the other is the Quranic commentary of Syed Qutb (1902 A.D – 1966 A.D) who belonged to Egypt and made great contribution in Islamic revival, a famous author and activist. “Tafheem ul Quran” is a famous commentary of the Holy Quran in Urdu language which has received acceptance among new generation and modern educators, while tafsir “Fi-Dhilal il-Quran” is written in Arabic language which is famous all over the world. In addition there is so many similarities and commonalities in the work of these two honourable scholars i.e. both has preaching style in their tafsirs furthermore both had addressed the contemporary modern and social issues, presented Islam in systematic, logical and rational way and they tried to make the Quranic instruction more easier for the new generation. They also appeal the mind of modern man while addressing contemporary issues and while trying to present applicability of Islam in modern age, so this research is designed in the context mentioned above.